Apontamentos sobre o estilo historiográfico de arthur cézar ferreira reis na obra a amazônia e a cobiça internacional (edição de 1982) - Pacheco, Alexandre [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2014)
The representation of the Portuguese, the Portuguese-Brazilians and the Brazilian people in A Amazônia e cobiça internacional showed what the historian Arthur Cezar Ferreira Reis intended by portraying them as heroic defenders of the Amazon between the 17tth and the 18th centuries. This representation, metaphorically based in the fight between the forces of virtue (represented by the Portuguese, the Portuguese-Brazilian and the Brazilian people) against the usurper forces (represented mainly by the Anglo-Saxon people), was drawn from a non-dialectical perspective, since foreigners were never definitively diverted from their objective to conquer the Amazon. This representation should, by the perspective of Arthur Reis' idea of extreme nationality, make the great men who were in the service of the defense of the Amazon to be seen as the most capable to establish a symbiosis with the environment and the human element present in the region. This fact should serve as an example of patriotism for both his readers and to actions of men who wished to defend the Amazon in the sixties.
Notes on arthur cezar ferreira reis's historiographical style in his work a amazônia e a cobiça internacional (1982 edition)
Keywords: Amazon; Colonization; Defense process; Miscegenation; Nationalism